Designers' guide to Eurocode basis of structural design, EN 1990 - Gulvanessian, H. (Designers' guides to the Eurocodes., 2012)
Eurocode is considered the primary document in the Eurocode suite and establishes for the structural Eurocodes the principles and requirements for safety and serviceability of structures. More importantly, EN 1990 must be applied whenever the Eurocodes 1 to 9 are used.